2016
DOI: 10.1007/s11431-016-6056-8
|View full text |Cite
|
Sign up to set email alerts
|

The rising star in photovoltaics-perovskite solar cells: The past, present and future

Abstract: Perovskite solar cell (PVSC), after its invention since 2009, has attracted tremendous attention from both academia and industry, because of its low cost, ease of manufacturing features and the sky-rocketing efficiencies being achieved within such a short period of time. Currently, the new efficiency record has reached 21.0%, comparable to that of the commercialized PV technologies developed for decades, such as multi-crystalline Si, CIGS and CdTe thin film solar cells. It is very possible that PVSCs would one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 159 publications
1
16
0
3
Order By: Relevance
“…The STIM mappings of ceria also were obtained using photo-thermal excitation through a contact mode scanning with a gold coated AFM probe (Multi75GD-G, Budget Sensors), as shown in Figure 8 around a pentagonal grain. Variation of thermal response in a grain shown in Figure 8b is similar to what we observed in Figure 7b, suggesting possible influence of topography on heat conduction, though the frequency variation in Figure 7c Finally, we show our preliminary results of STIM ionic mapping on CH3NH3PbI3, an emerging perovskite material for solar cells [45,46]. It has been reported that ionic motion in CH3NH3PbI3 occurs under light illumination or electric field [47], which has significant implication to its photovoltaic performance.…”
Section: Resultssupporting
confidence: 80%
“…The STIM mappings of ceria also were obtained using photo-thermal excitation through a contact mode scanning with a gold coated AFM probe (Multi75GD-G, Budget Sensors), as shown in Figure 8 around a pentagonal grain. Variation of thermal response in a grain shown in Figure 8b is similar to what we observed in Figure 7b, suggesting possible influence of topography on heat conduction, though the frequency variation in Figure 7c Finally, we show our preliminary results of STIM ionic mapping on CH3NH3PbI3, an emerging perovskite material for solar cells [45,46]. It has been reported that ionic motion in CH3NH3PbI3 occurs under light illumination or electric field [47], which has significant implication to its photovoltaic performance.…”
Section: Resultssupporting
confidence: 80%
“…For example, both reports indicated that the unfavorable energy barrier present at the interface of FTO/TiO 2 and TiO 2 /MAPbI 3 causes hysteresis in planar PSCs . The unbalanced charge extraction is also regarded as one of the key factors for the current hysteresis phenomenon in different structures of PSCs, which is supported by the fact that the charge accumulation strongly distorts the perovskite structure at the interface and causes pronounced hysteresis . Aiming to suppress the charge accumulation caused by TiO 2 , numerous strategies have been explored to reduce the energy offset for electron extraction at the TiO 2 /perovskite interface, and the deep trap density cause by defects in the TiO 2 film.…”
Section: Planar Etls In Regular (N–i–p) Pscsmentioning
confidence: 99%
“…Inorganic-organic halide perovskite solar cells have attracted enormous attention as a promising photovoltaic technology due to their high power conversion efficiencies (PCEs), simple fabrication procedures, and low-cost [1][2][3][4] . In just a few years after its emergence, the PCE of perovskite solar cells has increased from 3.8% to 22.1% 5,6 .…”
Section: Introductionmentioning
confidence: 99%